Beta2 Glycoprotein I derived peptides and their mechanism of tumor control - Smalley, Haley Elizabeth (Kansas State University, 2020)
Melanoma is one of the deadliest forms of skin cancer in the United States. The rate of melanoma diagnoses has been increasing steadily over the past few decades. The growth and survival of melanoma tumors is affected by many factors, including angiogenesis and the immune response. Angiogenesis, the growth of new blood vessels, is usually held in check by pro-angiogenic molecules such as vascular endothelial growth factor, and anti-angiogenic molecules such as soluble Flt-1 (sFlt-1). In addition, the serum protein Beta2 Glycoprotein I (β2-GPI) both increases and decreases angiogenesis depending on concentration and conformation. Angiogenesis can alter and be influenced by cells and cytokines produced by the immune response in the tumor. The immune response including tumor-associated macrophages (TAMs), can increase angiogenesis, while angiogenesis can control the phenotype of TAMS in the tissue. We hypothesized that peptides derived from the binding domain of β2-GPI could reduce melanoma growth by controlling angiogenesis and thus altering TAM phenotypes. We used a mouse melanoma model and cell culture to determine whether the β2-GPI-derived peptides regulate angiogenesis to control tumor growth. We found that the peptides reduced tumor growth by increasing the secretion of sFlt-1 in the tumors. As sFlt-1 is also secreted by macrophages and can affect macrophage polarization, we investigated whether the β2-GPI-derived peptides could alter macrophage phenotype. We examined this change in macrophage phenotype by examining RNA from tumors and bone marrow-derived macrophages (BMDMs) treated with β2-GPI-derived peptides. We found that treatment with β2-GPI decreased anti-inflammatory cytokines in BMDMs and altered inflammatory cytokines in the tumors as well. These data indicate that treatment with β2-GPI-derived peptides reduces melanoma growth through regulation of angiogenesis and changes in inflammatory response.
Keywords: Beta2 Glycoprotein I; Melanoma; Cancer; Immunology